POLA PERKECAMBAHAN RAMIN (Gonystylus bancanus) DAN EFEKTIFITAS KOMPOSISI MEDIA TANAM - Rachman, Erlin; Utami, Ning Wikan (Research Center for Biology-Indonesian Institute of Sciences, 2006)
A research work on seed germination of ramin (Gonystylus bancanus (Miq. Kurz) was conducted to study germination pattern and the effectivity of some composition of planting medias contained compost, cocopeat, organic manure, carbonic sekam and soil.The result showed that the seed germination pattern of ramin at least consist of six stages based on one or more morfological change or an organ formation occured. A growing period needed by the juvenil ramin to grow from a stage to next stage and the seedling plant heigh were taken as parameters to pursued the effectivity of planting media composition. Generally, media contained compost, cocopeat, carbonic sekam and organic manure were much more effective than medium contains soil only. Medium contained compost only was the most effective as planting media based on the two parameters. Cocopeat and carbonic sekam was also recommended as alternative planting media for seed germination and juvenil plant growth of ramin.